(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article critically analyzes the convenience aspects of fast food and its impact on health. It examines factors contributing to fast food consumption, including speed, affordability, and ease. The article discusses the nutritional composition of fast food, its high content of fat, sugar, and salt. Short-term and long-term health risks such as obesity, cardiovascular diseases, and depression are thoroughly analyzed. Socio-economic and cultural factors influencing consumption choices are also considered. Finally, state and individual strategies to promote healthier choices and and mitigate risks are proposed.